MONITORING AKTIVITAS PETANI DAN ANALISIS EKONOMI PERTANIAN SAYURAN ORGANIK DAN KONVENSIONAL PADA DAERAH DATARAN TINGGI BALI - MADE SUDANA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id)
The organic farming company produced yield continuously, weather-independent, theproduces in easily to sold at the hotel or supermarket with good price. However, in theorganic farming owned personally as well as conventional farming, the productionsignificantly influenced by weather and marketing access to hotel or restaurant is limited.Economic analysis of the three types of agriculture system showed that organicfarming with capital intensive as represented by Golden Leaf Farm Company, provide the netrevenue Rp. 15.855.750/year/0.1 ha with B/C ratio 3.9; Return on investment (ROI) 290%;net revenue/income ratio (RI) 0.74 and pay back period (PBP) 4 months. In the case of theorganic farming which managed personally, produced net revenue Rp. 1.005.762/year/0.1 hawith B/C ratio 1.6, ROI 64%, RI ratio 0.35 and PBP 26 months. On the other hand, in theconventional farming , the net revenue was Rp. 875.200/year/0.1 ha with B/C ratio 1.4, ROI40%, RI ratio 0.28 and PBP 30 months. In the conventional farming when farmers growing acombination between Vegetables and Potato, the net revenue increased to Rp.4.577.268/year/0.1 ha with B/C ratio 2.3, ROI 133%, RI ratio 0.54 and PBP 11 months.